Los análisis de los estados financieros en una empresa comercial, en Maynas, para una mejor toma de decisiones, periodo – 2019 - Hurtado Ruiz, Erika Viviana (2023)
In our thesis we have a favorable and satisfactory opinion, that the analyses to the statement of financial position and the statement of results of a commercial organization is important, and the purpose is the achievement of optimal and positive results for the company, which will benefit before external financiers for obtaining loans, our research work, "The analysis of financial statements in a commercial company, in Maynas, for better decision making period- 2019", this research is of Qualitative- Descriptive type, its study population was 25 people, stores and companies of purchases and sales of goods and services, which present their financial statements to SUNAT, SMV and financial institutions, to obtain loans. As researchers we reached 68% of efficient, this percentage recognizes that the analysis of the financial statements is fundamental in the companies, because they represent liquidity and profitability, according to its movement of its financial situation, 12% think deficient for the reason that many companies in our country do not apply these analyses or financial ratios at the end of preparing their financial statements, it will be for the tedious work of making them or for the amount of financial formulas that are used at the time of applying them. Finally, we believe that it is important to apply their analysis to the statement of financial position and income statement in all commercial organizations, so we have real results of the accounting and financial transactions of the organization, with positive results in the payment of taxes and financial institutions.